2017
DOI: 10.15226/2376-4589/3/1/00124
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacterial Lysates by Use of Matrix-Assisted Laser Desorption– Ionization Time of Flight Mass Spectrometry Fingerprinting

Abstract: Bacterial lysates have for long been used to boost the immunological response to Respiratory Tract Infections (RTI) both in children and adults. They are prepared by growing bacteria usually associated with RTI, followed by chemical or mechanical disruption to prepare single bacterial lysates that are combined in the final product. Despite the wide range of applications, one drawback for their universal use is the difficulty to assure consistency in their composition given their particular form of preparation;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…In addition, SDS-PAGE analysis of individual bacterial lysates, showed that those prepared by mechanical disruption show larger number and more defined protein bands, whereas alkaline lysates showed a smear in the SDS-PAGE ( Supplemental Figure 2 ). In line with this, we have also recently showed elsewhere that MALDI-TOF spectra revealed more proteins abundance and with greater intensity in the PMBL compared to PABL ( 29 ). For use in comparative analysis PABL were further concentrated as to have the same amount of total proteins than PMBL.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, SDS-PAGE analysis of individual bacterial lysates, showed that those prepared by mechanical disruption show larger number and more defined protein bands, whereas alkaline lysates showed a smear in the SDS-PAGE ( Supplemental Figure 2 ). In line with this, we have also recently showed elsewhere that MALDI-TOF spectra revealed more proteins abundance and with greater intensity in the PMBL compared to PABL ( 29 ). For use in comparative analysis PABL were further concentrated as to have the same amount of total proteins than PMBL.…”
Section: Resultssupporting
confidence: 86%
“…Most descriptions of commercial lysates, either in the literature or in patent filling just quantifies proteins and carbohydrates (5,(34)(35)(36). We have recently proposed that the use of MALDI-TOF technique for characterization and identification of biomarkers of biological activity that helps to evaluate the consistency and reproducibility of batch production would represent an advance in this sense (29). Vaccine-induced protection against pneumonia relies on neutrophils that kill anti-capsular antibodies-opsonized bacteria (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%